Rotational Thromboelastometry Reduces Fresh Frozen Plasma Requirement in Patients without Liver Disease Undergoing Therapeutic Endoscopic Procedures with Deranged Screening Coagulation Tests—A Pilot Study - Bharadwaj, P. Krishna; Simon, Ebby George; Dave, Rutvi G.; Geevar, Tulasi; Nair, Sukesh C.; Abraham, Aby; Joseph, A. J.; Dutta, Amit Kumar; Chowdhury, Sudipta Dhar; Jaleel, Rajeeb; John, Anoop; Thomas, Ajith (Journal of Digestive Endoscopy, 2023)
Background/Aims Rotational thromboelastometry (ROTEM) is a viscoelastic test that is used in patients with liver disease for guiding blood component use. This study is aimed at comparing the amount of blood products transfused and bleeding rates in patients without liver disease, who underwent therapeutic endoscopic procedures with deranged screening coagulation tests (prothrombin time [PT]; activated partial thromboplastin time [aPTT]), with and without hypocoagulable ROTEM.Methods Patients with deranged PT and aPTT without liver disease who underwent therapeutic endoscopic interventions during the period 2020 to 2022 were retrospectively analyzed. Baseline parameters, amount of blood products transfused, and outcomes such as 30-day bleeding and mortality rates were recorded in those with and without hypocoagulable ROTEM.Results Of the 204 patients with deranged PT/aPTT who underwent therapeutic endoscopy during the study period, 180 of those with liver disease were excluded. Six patients (M:F = 5:1; median age: 37, 20–54 years) had hypocoagulable ROTEM and 18 patients (M:F = 11:7; median age: 56, 20–71 years) had normo-/hypercoagulable ROTEM. There were significant differences in the total amount of fresh frozen plasma (FFP) transfused and FFP transfused per patient between the two groups (9,000 vs. 4,500 mL and 2,000 vs. 1,000 mL; p = 0.04, respectively). Two patients with hypocoagulable ROTEM bled within 30 days, while none did in the comparator group (p = 0.03). One patient in the hypocoagulable group died within 30 days and none in the normo-/hypercoagulable group.Conclusion The use of ROTEM reduces FFP requirement in patients without liver disease with deranged PT/aPTT undergoing therapeutic endoscopic procedures without any increased risk of early or late rebleeding, and 30-day mortality.
Keywords: fresh frozen plasma; rebleeding; screening coagulation tests; therapeutic endoscopic procedures; thromboelastometry